What we talk about when we talk about new media: digital subjectivity and Tao Lin's Taipei. Issue 8 (2nd August 2020) - Sheu, Chingshun J.
ABSTRACT: New media studies has often focused on the difference between traditional and new media objects while neglecting the perspectival difference in worldview and subjectivity concomitant with the becoming-ubiquitous of the digital. In this paper, I first illustrate with some examples from science fiction the complex relation between difference in kind and difference in degree. This allows me to examine why some well-known demarcations between traditional and new media seem blurry and untenable. There is, however, one line of cleavage that does hold water: the binary of analogue and digital proposed by N. Katherine Hayles. To see why, I compare works of fiction that present media technologies via analogue subjectivity with Tao Lin's Taipei, a novel that presents lived experience through digital subjectivity, thereby revealing the continuing potential of new media studies for literature.